PERAN GURU DALAM MENDORONG KREATIVITAS SISWA GEN Z DI ERA DIGITAL - Rahman, Anisa; Arifin, Juliana Dwi; Sartika, Rinny (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2024)
The development of digital technology has brought significant changes in the world of education, particularly in the way Generation Z students learn and interact in the classroom. Teachers play a crucial role in fostering student creativity in the digital era, where access to information is easily obtained. However, the challenge lies in how teachers can effectively integrate technology to support student creativity in learning. The aim of this study is to explore the role of teachers in encouraging the creativity of Gen Z students in the digital era. This research employs qualitative methods by collecting data from journals, books, and other sources. The findings reveal that teachers play a crucial role in creating a learning environment that supports creativity, especially by utilizing technology. Teachers who can adapt to technological advancements are proven to be more effective in facilitating creative learning. The discussion also highlights the importance of teacher training in the use of technology as a teaching tool, enabling students to explore their creative ideas optimally.